MAPPING DETERMINANTS OF COMPLIANCE WITH PARTOGRAPH DOCUMENTATION AND AMTSL IMPLEMENTATION IN CHILDBIRTH SERVICES - Siti Aminah; Fauzia Laili; Dessy Lutfiasari; Siswi Wulandari (Journal for Quality in Women's Health, 2026)
Compliance with partograph documentation and AMTSL varies across childbirth services. Objective: To map determinants influencing compliance. Methods: A PRISMA-ScR/JBI scoping review searched PubMed, Scopus, ProQuest, and DOAJ and checked reference lists. Results: Of 630 records, 142 duplicates were removed; 76 full texts were assessed; and 22 studies were included (14 quantitative, 5 qualitative, 3 mixed-methods). Determinants clustered into five domains: provider factors (knowledge, skills, fatigue), organizational factors (supportive supervision, staffing, audit-feedback), system/policy factors (SOP clarity, guideline dissemination), resources/logistics (forms, monitoring equipment, uterotonics), and workflow/documentation processes (time constraints, documentation burden, duplication). Conclusion: Improving compliance requires strengthening both provider competence and enabling systems, alongside standardized compliance indicators.